calculus

posted by .

Evaluate each of the following. Show all your calculations.

f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6

  • calculus -

    All these question are of the same easy type that your were helped with repeatedly yesterday.
    You did not respond to any of our answers.
    Exactly where does your difficulty lie ?

    Show me your steps that you tried to solve this problem.

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calculus

    Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
  2. biology

    Given the part of the molecule shown below, can the underlined atom participate in a hydrogen bond with an approriate bonding partner?
  3. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  4. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  5. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. a) f'(3) if f(x)  = x^4 − 3x b) f' (−2) if f(x) = 2x^3 + 4x^2 − 5x + 8 c) f" (1) if f(X)  = −3x^2 − 5x + 7 …
  6. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11
  7. calculus

    Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6
  8. calculus (gr 12)

    Evaluate each of the following. Show all your calculations. f" (−3) if f(x)  = 4x^3 − 3x^2 + 2x − 6
  9. calculus

    Evaluate each of the following. Show all your calculations. f′ (3/4)if f(x) = −3x^3 − 7x^2 + 4x − 11
  10. Grade 12 Calculus

    Evaluate each of the following. Show all your calculations.  f" (1/3) if f(x) = −2x^5 + 2x − 6

More Similar Questions